Gestão pública por resultados: um estudo de caso na Prefeitura Municipal do Recife - AQUINO, Vanessa de Almeida (2023)
A movement to modernize public management is underway around the world, and although the scope and objective of the reforms vary from one country to another, in general they aim to transform models centered on rules and processes into systems that give importance to citizen satisfaction and are oriented towards a commitment to results in society. As a natural consequence of this continuous process of improvement, in Brazil, the management by results practices have been replicated in various federal spheres, including municipalities, which perform an essential role in the formulation and execution of public goods and services for the population. However, the implementation and institutionalization of these mechanisms requires attention so that adjustments and adaptations during their execution do not detract from their initial objectives, since the main bottlenecks in terms of management are found in the municipal sphere, but it is also in this sphere where the results of good models developed are more evident, with faster final results. In this way, this research has undertaken a descriptive study with a qualitative methodological approach with the aim of analyzing, based on a case study, the strategies adopted to implement and institutionalize Management by Results (MBR) in the Municipality of Recife, which in addition to contributing to the improvement of the specific case, has empirical relevance for public management, especially in municipalities. To this end, data collection included semi-structured interviews, direct observation, bibliographic analysis and documentary research. The results show that the implementation of MBR in the entity analyzed had a comprehensive and multifaceted approach, involving the preparation of municipal strategic planning, agreement on goals and their respective performance indicators, creation of a new organizational structure, appointment of new civil servants, development of governance tools and preparation of a monitoring and evaluation system, along with reward mechanisms in some secretariats. However, despite the progress made, the development of the MBR system in the municipality still faces difficulties and there are areas in need of improvement. These challenges cover several dimensions, such as the large number of indicators, difficulty in accessing structured information, the need for integration between units and leadership, resistance to change on the part of employees, the need to train teams to meet new demands, resource limitations and the lack of specific regulatory guidelines which can make it difficult to institutionalize management by results practices. The findings also indicate that the Management by Results culture is gradually being internalized in the organization, which is understandable given that the model is relatively new. Thus, although notable progress has been made in implementing the practices, overcoming these challenges and areas for improvement will require continued efforts, investments in technology, training, integration policies and the establishment of solid regulations.